Communication—Indentation of Li-Ion Pouch Cell: Effect of Material Homogenization on Prediction of Internal Short Circuit. Issue 10 (12th September 2016) - Kumar, A.; Kalnaus, S.; Simunovic, S.; Gorti, S.; Allu, S.; Turner, J. A.
Abstract : We performed finite element simulations of spherical indentation of Li-ion pouch cells. Our model fully resolves different layers in the cell. The results of the layer resolved models were compared to the models available in the literature that treat the cell as an equivalent homogenized continuum material. Simulations were carried out for different sizes of the spherical indenter. We show that calibration of a failure criterion for the cell in the homogenized model depends on the indenter size, whereas in the layer-resoled model, such dependency is greatly diminished.